A Case of Sirenomelia Associated with Hypoplastic Left Heart with a Healthy Co-Twin: A Rare Entity - Houda Nasser Al Yaqoubi; Muna Mubarak Al Badi; Farida Mohsin Ambu Saidi; Nasser Shaikhan Taaeeb Al Shafouri (Case Reports in Pediatrics)
Sirenomelia is a rare developmental malformation and is incompatible to life. The incidence of sirenomelia, as recorded in the literature, is estimated to be approximately between 1.5 and 4.2 per 1,00,000 births. Around 15% of sirenomelia cases are associated with twin pregnancy, most often in monozygotic cases with an incidence of 7%. In monozygotic twins, the risk of sirenomelia is nearly 100–150 times higher as compared to dizygotic twins or singleton pregnancies. Until now, only two cases of sirenomelia associated with hypoplastic left heart have been reported in the literature. Here, we present a monozygotic twin pregnancy, where one fetus was diagnosed with sirenomelia associated with hypoplastic left heart syndrome and the co-twin was absolutely healthy.